Analisis Tingkat Ketercapaian Kompetensi Pedagogi Dan Profesional Guru SMP Negeri 1 Hu’u Dompu - Sofyan Syamratulangi; Agus Tinus (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: Teachers' pedagogical and professional competencies are important to develop. In the 21st century teachers are required to build effective relationships with students and the school community by using technology to improve the quality of education. This study aims to 1) analyze the level of achievement of pedagogical and professional competence of teachers in Junior High School 1 Hu'u. 2) Describe the obstacles in increasing the level of achievement of the pedagogical and professional competence of teachers in Junior High School1 Hu'u. 3) Efforts made in overcoming obstacles to increasing the achievement of pedagogical and professional competence of teachers in Junior High School 1 Hu'u. This research used a mix method approach (a combination of qualitative methods with quantitative methods) with the type of case study research. The research location is Junior High School 1 Hu'u, Dompu Regency, West Nusa Tenggara. Questionnaire data collection techniques, interviews, documentation, and observation. The information is the principal and thirty teachers who are used as primary data and secondary data. Data collection techniques for data reduction, data presentation, drawing conclusions and validity of the data. The results showed that 1) the level of pedagogical competence and professional competence of teachers at Junior High School 1 Hu'u was sufficient and sufficient to be called a professional teacher. 2) The obstacle faced by teachers in developing pedagogical and professional competencies is that there is diversity in the ability of teachers in the learning process and mastery of knowledge and many GTT teachers who have long taught at Junior High School 1 Hu'u have not received NUPTK. 3) Efforts are made to improve the pedagogical and professional competence of teachers, namely through teacher development training conducted every weekend such as KKG, MGMP activities.Keywords: Pedagogical Competence, Professional Competence, Achievement Abstrak: Kompetensi pedagogi dan profesional guru saat ini penting untuk dikembangkan.Pada abad 21 guru dituntut membangun hubungan yang efektif dengan siswa dan komunitas sekolah dengan menggunakan teknologi untuk peningkatan mutu pendidikan. Penelitian ini bertujuan untuk 1) melakukan analisis tingkat ketercapaian kompetensi pedagogi dan profesional guru yang ada di SMPN 1 Hu’u.2) Mendeskripsikan hambatan dalam meningkatkan tingkat ketercapaian kompetensi pedagogi dan profesional guru yang ada di SMPN 1 Hu’u. 3) Upaya yang dilakukan dalam mengatasi hambatan peningkatan ketercapaian kompetensi pedagogi dan profesional guru yang ada di SMPN 1 Hu’u.Penelitian ini menggunakan pendekatan mix method (gabungan metode kualitatif dengan metode kuantitatif) dengan jenis penelitian studi kasus.Lokasi penelitian di SMPN 1 Hu’u Kabupaten Dompu Nusa Tenggara Barat. Teknik pengumpulan data angket, wawancara, dokumentasi dan Observasi. Informannya kepala sekolah dan tigapuluh guru yang dijadikan sebagai data primer dan data sekunder. Teknik pengumpulan data reduksi data, penyajian data,penarikan kesimpulan serta keabsahan data. Hasil penelitian menunjukkan bahwa tingkat ketercapain kompetensi pedagogi dan kompetensi profesional guru SMPN 1 Hu’u sudah memadai dan cukup syarat dikatakan sebagai guru profesional. Hambatan yang dihadapi guru dalam mengembangkan kompetensi pedagogi dan profesional yaitu adanya keberagaman kemampuan guru dalam proses pembelajaran dan penguasaan ilmu pengetahuan danbanyak guru GTT yang sudah lama mengajar di SMPN 1 Hu’u belum mendapatkan NUPTK. Upaya yang dilakukan dalam meningkatkan kompetensi pedagogi dan profesional guru yaitu dengan pelatihan pengembangan guru yang dilakukan setiap akhir pekan seperti kegiatan KKG, MGMP.Kata kunci: Kompetensi Pedagogi, Kompetensi Profesional, Ketercapaian